Intracranial Pulsatility in Relation to Severity and Progression of Cerebral White Matter Hyperintensities. Issue 11 (November 2020) - Kneihsl, Markus; Hofer, Edith; Enzinger, Christian; Niederkorn, Kurt; Horner, Susanna; Pinter, Daniela; Fandler-Höfler, Simon; Eppinger, Sebastian; Haidegger, Melanie; Schmidt, Reinhold; Gattringer, Thomas
Abstract : Background and Purpose: Previous studies suggested an association between increased intracranial arterial pulsatility and the severity of microangiopathic white matter hyperintensities (WMH). However, possible confounders such as age and hypertension were seldomly considered and longitudinal data are lacking. We here aimed to explore whether increased middle cerebral artery pulsatility is associated with baseline severity and progression of cerebral small vessel disease–related WMH in elderly individuals. Methods: The study population consisted of elderly participants from the community-based ASPS (Austrian Stroke Prevention Study). Baseline and follow-up assessment comprised transcranial Doppler sonography, brain magnetic resonance imaging, and clinical/laboratory examination of vascular risk factors. Pulsatility index on transcranial Doppler sonography was averaged from baseline indices of both middle cerebral arteries and was correlated with baseline WMH severity and WMH progression over a median follow-up period of 5 years in uni- and multivariable analyses. WMH severity was graded according to the Fazekas scale, and WMH load was quantified by semiautomated volumetric assessment. Results: The study cohort comprised 491 participants (mean age: 60.7±6.9 years; female: 48.5%). Pulsatility index was increased in participants with more severe WMH at baseline ( P <0.001) but was not associated with WMH progression during follow-up (rs : 0.097, P =0.099). In multivariable analyses, only arterial hypertension remained significantly associated with baseline severity ( P =0.04) and progression ( P =0.008) of WMH, although transcranial Doppler sonography pulsatility index was not predictive ( P >0.1, respectively). Conclusions: This community-based cohort study of elderly individuals does not support the pulsatility index of the middle cerebral artery on transcranial Doppler sonography as an independent marker of microangiopathic WMH severity and progression over time.